Comparison of the Patient Diagnostic Yield of Fibre-optic Bronchoscopy with Conventional Tracheal Aspirate - Dhakal, Subodh Sagar; Mishra, Navin Kumar; Bhatta, Karuna; Shrestha, Milan; Karna, Rohit; Khanal, Arjan (Journal of BP Koirala Institute of Health Sciences, 2020)
Objective: To know the efficacy of Bronchoalveolar Lavage (BAL) in establishing diagnosis and its impact on overall health status of the patients.Methods: A single center, longitudinal study involving 40 patients aged > 18 years old with septic shock with similar baseline characteristics was conducted. Two study arms, 20 patients in intervention arm - patient with utilization of Bronchoscopy and BAL in aiding diagnosis and 20-patients in conservative- arm without Bronchoscopy were compared in terms of establishing diagnosis primarily and secondarily in terms of length of stay and 30-day mortality. We were able to identify following organisms in BAL sample: Mycobacterium tuberculosis- 4, Acinetobacter baumanii- 3, Pseudomonasaeruginosa- 2, Klebsiella oxytica- 2, E. coli- 2, Streptococcus pneumoniae- 2, Staphyloccus aureus-Results: We were able to identify various infectious agents as mentioned above 16/20 in BAL group compared to 8/20 in conventional arm; neoplasm in 4 out of 20 subjects in BAL group. In 80% of cases, BAL helped in identifying the organisms compared to only 40% in tracheal aspirate group. In addition, six cases in Intervention arm vs. nine cases in conventional arm had more than > 14 days hospital stay with the p-value 0 .492091. Interventional arm had lesser mortality 5 cases vs. 7 cases in Conventional arm with the p-value of 0.490153 which was not statistically significant.Conclusion: We conclude that the diagnostic bronchoscope and related procedures among critically ill patients are helpful in identifying the pathogens and in detecting malignancy.